Exploring Research Trends On Foreign Direct Investment : A Bibliometric Study - Eka Indah Nurlaili; Waspodo Tjipto Subroto; Norida Canda Sakti (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
The purpose of this study is to identify and analyze trends in the most relevant scientific work being conducted on the topic of foreign direct investment. In addition, an exploration of this topic is carried out in a way that allows the expansion of empirical and conceptual knowledge. A bibliometric analysis was carried out using the Bibliometrix and Biblioshiny software packages on academic articles indexed in the Scopus database. Search criteria were applied, initially resulting in a total of 8,115 articles in the period 2013–2023. Finally, after applying exclusion criteria, a total of 1361 interesting and valid articles were obtained. The results of this study present important relevant topics in the topic of foreign direct investment, provide a quantitative analysis that provides an overview of the research topic on foreign direct investment presenting tables, graphs and maps, and identify key performance indicators for article production and citations. The findings of this study are that articles centered on this concept have gained significant traction, forming the basis for efforts aimed at improving the concept of sustainable investment in the context of the various variables that influence it.